2019
DOI: 10.1002/wat2.1348
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the riverine pulse: Applying high‐frequency nitrate data to advance integrative understanding of biogeochemical and hydrological processes

Abstract: Widespread deployment of sensors that measure river nitrate (NO 3 −

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 173 publications
(482 reference statements)
1
93
0
Order By: Relevance
“…The fine temporal scale observations of in-stream concentrations provided by high-temporal nutrient loggers have transformed our understanding of in-stream processes, especially for nitrogen (Burns et al, 2019). The high frequency sampling provided by data loggers has shown that diel patterns in N signals can be out of phase with the timing of metabolic signals indicated by dissolved oxygen diel cycles (Hensley & Cohen, 2016;Nimick, Gammons, & Parker, 2011).…”
Section: High-temporal Sensors and The Impact On Understanding Nutrmentioning
confidence: 99%
See 2 more Smart Citations
“…The fine temporal scale observations of in-stream concentrations provided by high-temporal nutrient loggers have transformed our understanding of in-stream processes, especially for nitrogen (Burns et al, 2019). The high frequency sampling provided by data loggers has shown that diel patterns in N signals can be out of phase with the timing of metabolic signals indicated by dissolved oxygen diel cycles (Hensley & Cohen, 2016;Nimick, Gammons, & Parker, 2011).…”
Section: High-temporal Sensors and The Impact On Understanding Nutrmentioning
confidence: 99%
“…Nutrient sensors have the potential to unravel some of the complexities of signals in urban streams and other disturbed systems (Burns et al, 2019;Pellerin et al, 2016). High temporal data have allowed for detailed storm analysis of nutrient dynamics, with concentration-discharge relationships being used to evaluate sources of nutrients to streams (Burns et al, 2019).…”
Section: High-temporal Sensors and The Impact On Understanding Nutrmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while a lumped hydrologic and nitrogen model that provides continuous estimate of pathway loading is robust (Hartmann et al, 2016; Husic, Fox, Adams, Ford, et al, 2019; Sullivan et al, 2019), there are less model‐intensive alternatives such as loadograph separation (Fenton et al, 2017; Mellander et al, 2012; Miller et al, 2017). Loadograph separation only requires nitrate concentration and discharge, which are commonly becoming ubiquitous, particularly with the widespread use of aquatic nitrate sensors that provide continuous estimates of nitrate concentration (Burns et al, 2019). Further, with regard to nitrate sourcing, stable isotopes are commonly employed (Lutz et al, 2019; H. Zhang, Kang, et al, 2020; Wang et al, 2020; Z. Zhang, Chen, Cheng, Li, et al, 2020; Z. Zhang, Chen, Cheng, & Soulsby, 2020) but sources have also been unmixed with elemental concentration data alone (Katz et al, 2011; Yue et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…To summarize, high-resolution sensing of nitrate data has shown utility in quantifying diel, event, and longer-term N loading dynamics (Heffernan and Cohen, 2010;Pellerin et al, 2012Pellerin et al, , 2014Carey et al, 2014;Burns et al, 2016;Rode et al, 2016) and improved assessments of nitrate biological processing, including continuous estimates of biotic processing rates in streams (Heffernan and Cohen, 2010;Rode et al, 2016) and the ability to partition and better understand sources and pathways of nitrate loading at the watershed scale (Koenig et al, 2017;Kraus et al, 2017;Miller et al, 2017;Wollheim et al, 2017). Despite this, few studies have assessed the utility of these data to improve numerical water quality models (Burns et al, 2019;Jiang et al, 2019). Based on the utility of high-resolution nitrate data to quantify in situ biochemical processes and improve the characterization of nutrient loadings at reach and watershed scales (table A2), we investigated the utility of integrating high-resolution data streams with models in order to quantify the nitrate budget of confluence floodplain wetlands.…”
mentioning
confidence: 99%